IN DEFENCE OF CONTEXT-SENSITIVE SEMANTICS AND CONTEXT-SENSITIVE LINGUISTICS IN PRAGMATICS - Damatius Wagiman Adisutrisno (Widya Mandala Surabaya Catholic University, 2015)
Kinneavy (1971:23) states that “since pragmatics is viewed as the study of complete discourse, it does not include semantics as such or syntactic as such. These two constitute linguistics, and linguistic analysis is not discourse analysis, though, of course, it can contribute to the understanding of discourse, consequently, syntactic and semantics are beyond the borders of discourse study”. Cook (1990:12) also separates linguistics from discourse analysis. Linguistics is said to be without context or context-free. He further says that semantics is context-free. This paper is to argue that both sentence linguistics and semantics are context sensitive. From the point of view of language acquisition, the syntactic structures word meaning, sentence meaning and knowledge of the world that an informant later uses to produce language, are all based on context and are derived from context. Accordingly, sentence linguistics and semantics are context-sensitive. Key Words: pragmatics, linguistics semantics, context-sensitive